Peripheral nerve injury induces an immunometabolic signature involving reduced free fatty-acid pools - Jun Seo Park; Hye Won Jun; Jaesung Lee; Sung Joong Lee (Metabolic Brain Disease, 2026)
Peripheral nerve injury-induced persistent pain hypersensitivity cannot be fully explained by increased neuronal excitability alone. Rather, it is increasingly recognized as a pathological tissue state characterized by sustained glial activation, immune signaling, and synaptic remodeling within the spinal cord. In this context, metabolic remodeling of the spinal cord has emerged as a potentially important feature of neuropathic pain. However, the metabolic patterns associated with this state, and their relationship to underlying molecular programs, remain incompletely defined. Here, we performed GC–MS-based untargeted metabolomic profiling of the spinal cord dorsal horn on day 7 after spinal nerve transection (SNT). To provide orthogonal validation, we integrated pathway-analysis results from four independent spinal cord RNA-sequencing datasets derived from distinct neuropathic pain models and further conducted qPCR-based validation. Metabolic profiling revealed a clear separation between SNT and sham samples, marked by broad depletion of the free fatty acid pool and features consistent with an immunometabolic shift. Consistently, analyses across RNA-sequencing datasets and qPCR validation demonstrated upregulation of immune and inflammatory programs, together with downregulation of fatty acid metabolism and cholesterol homeostasis. Collectively, these findings suggest that persistent neuropathic pain should be interpreted not simply as a consequence of neuronal and immune signaling, but also through the metabolic tissue environment that supports and sustains this pathological state.